Impediments to Tort Liability in Islamic Jurisprudence (College of Basic Education Research Journal, 2025)
In Islamic jurisprudence,  "theory of guarantee" refers to  topic of exemptions from tort liability, which is considered one of the fundamental subjects in civil law. Study seeks to explore  cases and reasons that exempt individuals from bearing legal and moral responsibility for  damages  caused, despite  existence of a harmful act .Research examines  exemptions from tort liability related to personal capacity and competence, including natural and acquired impairments .Study concludes that exemptions from tort liability serve as a safeguard to achieve  balance between protecting  injured party and preventing  excessive imposition of responsibility on individuals for their actions.